Farmers' participation in small-scale irrigation in Amhara region, Ethiopia - Getasew Daru; Degsew Melak; Wondim Awoke; Sinkie Alemu (Cogent Economics & Finance, 2023)
Irrigation has a critical role in improving food security and alleviating poverty. Long-term studies on small-scale irrigation have identified several factors that influence the participation of farmers in irrigation. However, farmers in the study area are still hesitant to participate in small-scale irrigation as a source of income. As a result, the focus of this study was examining farmers' engagement in small-scale irrigation. A stratified random sampling technique was used to select 184 respondents, and data was collected from those sample respondents. The double hurdle model was used to identify determinants and the extent of farmers' participation in small-scale irrigation. The model's first hurdle found that farmers' desire to participate in small-scale irrigation was highly influenced by their age (1.3%), educational level, extension contact (20.8%), training access (19.7%), dependency ratio, farm distance from water, and land topography. According to the result of the second hurdle, the level of farmers' participation in small-scale irrigation was highly affected by land size (11.6%), income, adult labor, educational level, age, and market distance. The study finds that strengthening income sources, land utilization, training access, extension contact, market access, and education level would increase farmer participation in small-scale irrigation. Therefore, stakeholders should strive to deliver these essential services to encourage farmers to participate in small-scale irrigation.
Keywords: 330; determinants; double hurdle; extent; participation; small-scale irrigation